Which Surgery in Geriatric Breast Cancer - Giorgio Maria Paul Graziano; Prof Antonino Graziano (Journal of Surgery and Surgical Research - Peertechz Publications, 2016)
Introduction: The improved living and environmental conditions have resulted in an increase in life expectancy with greater observation of breast cancer in elderly. The present study, through a retrospective analysis of our series, compares the results of treatment in two similar groups of patients under 75 (65-75) and over 75 (76-85) years of age, evaluating the efficacy and complications of locoregional and general therapy in relationship to biological age, associated diseases, and also the influence on the results of the cultural level and lifestyle. Materials and Methods: The criteria that we evaluated retrospective 110 patients are: age (65-85) with mean age 75, of which 69.8% aged between 65-75 while the remaining 30.2% aged between 75-85 years; The TNM, distributed among the patients as: stage I, 5 (4.5%), stage II No 56 (50.9%), stage III No 30 (27.3%) stage IV No. 19 (17.2 %). Associated diseases. Considered in the two groups were BPCO hypertension, cerebrovascular disease, BMI pathological. Results: Surgical treatment was mastectomy, QUART, lumpectomy. And search for the sentinel node. The evaluation excluded patients treated on tumorectomy and mastectomy. Complications, shown in Tables 1, have been modest. Perioperative mortality was absent. Discussion: In geriatric patients with breast cancer it is significantly detected as our series. This finding raises the question of what therapeutic strategy should be implemented to overcome the line of thought that suggests a limited therapeutic treatment, and therefore presumably inadequate. TheTNM staging effective to determine the true extent of the disease is essential to avoid a therapeutic treatment is not appropriate, without unnecessary unless a truly effective treatment for elderly patients Conclusions: In the treatment of patients with geriatric breast cancer, TNM cancer criteria were adopted without removing other as ASA 'Karnosky Index. This therapeutic approach, beyond old age, considered almost a marginal factor, obtained satisfactory results with a lengthening of life expectancy.